Manajemen talenta terintegrasi / Ernie Tisnawati Sule, Ratri Wahyuningtyas; editor, Putri Christian - ERNIE TISNAWATI SULE, 1954-; Ratri Wahyuningtyas; Putri Christian (Andi, 2016)
xii, 257 hlm. : ilus. ; 23 cm.